Skin absorption of felbinac solid nanoparticles in gel formulation containing l-menthol and carboxypolymethylene - Reita Kadowaki; Fumihiko Ogata; Aoi Fushiki; Saki Daimyo; Saori Deguchi; Hiroko Otake; Mayumi Nagata; Hiroshi Sasaki; Naohito Kawasaki; Noriaki Nagai (BMC, 2023)
Abstract Background It is important to design an effective formulation to enhance the skin penetration, and nanotechnologies have been used in dermal and transdermal drug delivery. In this study, we prepared formulations (gels) containing l-menthol and felbinac (FEL) solid nanoparticles (FEL-NP gel) for topical application, and investigated the local and systemic absorption of the prepared FEL-NP gel. Methods FEL solid nanoparticles were obtained by bead milling of FEL powder (microparticles), and a topical formulation (FEL-NP gel) consisting of 1.5% FEL solid nanoparticles), 2% carboxypolymethylene, 2% l-menthol, 0.5% methylcellulose, and 5% 2-hydroxypropyl-β-cyclodextrin (w/w %) were prepared. Results The particle size of FEL nanoparticles was 20-200 nm. The released FEL concentration from FEL-NP gel was significantly higher than that from FEL gel without bead mill treatment (carboxypolymethylene gel in which FEL microparticles (MPs) instead of FEL nanoparticles were incorporated, FEL-MP gel), and FEL was released as nanoparticles from the gel. Moreover, both transdermal penetration and percutaneous absorption of FEL-NP gel were significantly increased compared with those of FEL-MP gel, and the area under the FEL concentration-time curve (AUC) of FEL-NP gels was 1.52- and 1.38-fold of commercially available FEL ointment and FEL-MP gel, respectively. In addition, after 24 h of treatment, the FEL content in rat skin treated with FEL-NP gels was 1.38- and 2.54-fold higher than that when treated with commercially available FEL ointment and FEL-MP gel, respectively. Moreover, the enhanced skin penetration of FEL-NP gels was significantly attenuated by inhibition of energy-dependent endocytosis, such as clathrin-mediated endocytosis. Conclusions We successfully prepared a topically applied carboxypolymethylene gel containing FEL nanoparticles. In addition, we observed that the endocytosis pathway was mainly related to the high skin penetration of FEL nanoparticles, and FEL-NP gel application resulted in high local tissue concentration and systemic absorption of FEL. These findings provide useful information for the design of topically applied nanoformulations against inflammation by providing local and systemic effects.